2020
DOI: 10.1111/infa.12333
|View full text |Cite
|
Sign up to set email alerts
|

Familiarity plays a small role in noun comprehension at 12–18 months

Abstract: Infants amass thousands of hours of experience with particular items, each of which is representative of a broader category that often shares perceptual features. Robust word comprehension requires generalizing known labels to new category members. While young infants have been found to look at common nouns when they are named aloud, the role of item familiarity has not been well-examined. This study compares 12-18-month-olds' word comprehension in the context of pairs of their own items (e.g. photos of their … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 44 publications
2
12
0
Order By: Relevance
“…This analysis window reflects a period of time when the average curve in the uncorrected timing data begins to deviate from chance to a point in time when the confidence bands do not include chance responding (Figure 2). Importantly, this time period occurs earlier than we would normally expect to see eye gaze behavior in response to the spoken words with most studies approximating looking behavior to begin around 300 ms (e.g., Fernald et al, 1998;Swingley and Aslin, 2002;Fernald et al, 2008;Garrison et al, 2020). We expected that in-person LWL data, as represented by a Peekbank sample, would have significantly later shifts to the target than the uncorrected Zoom LWL data.…”
Section: Time Course Of Looking Behaviormentioning
confidence: 91%
“…This analysis window reflects a period of time when the average curve in the uncorrected timing data begins to deviate from chance to a point in time when the confidence bands do not include chance responding (Figure 2). Importantly, this time period occurs earlier than we would normally expect to see eye gaze behavior in response to the spoken words with most studies approximating looking behavior to begin around 300 ms (e.g., Fernald et al, 1998;Swingley and Aslin, 2002;Fernald et al, 2008;Garrison et al, 2020). We expected that in-person LWL data, as represented by a Peekbank sample, would have significantly later shifts to the target than the uncorrected Zoom LWL data.…”
Section: Time Course Of Looking Behaviormentioning
confidence: 91%
“…This in-the-moment behavior draws on a child's lexicon, requiring recollection of prior knowledge and, critically, an application of such knowledge in real time. By around one year of age, children can do this, correctly attending to a known target when presented with its auditory label (Oviatt, 1980;Woodward, Markman & Fitzsimmons, 1994); a process which becomes efficient between 17-and 24-months (Fernald, Pinto, Swingley, Weinbergy & McRoberts, 1998) and is seen both in the home and lab (Garrison, Baudet, Breitfeld, Aberman & Bergelson, 2020).…”
Section: Timescales Of Word Learningmentioning
confidence: 99%
“…That fact is underscored herecaregivers reported that all children knew the known items used, but children still varied quite remarkably in their ability to bring such knowledge to bear in the lab setting. In fact, recent laboratory tests recognize this variability, showing that while, overall, children do recognize "known" items in the lab, there is a bias for specific familiar exemplars (Garrison et al, 2020), suggesting that representation of known items may still be weak in some ways. What the current work adds is that overall vocabulary size predicts the use of any individual word in a given moment.…”
Section: Implications For Lt Childrenmentioning
confidence: 99%
“…Additionally, to ensure that the coarse division of the analysis window into five distinct time bins did not obscure more fine-grained differences across conditions, we analyzed infants' looking patterns using growth curve analysis. The data were aggregated into 50-ms bins, empirical logit transformation was applied to the proportion of target looking in each bin ( ptl = T/(T + D); T: total target looking; D: total distractor looking; elog = log[( ptl + 0.5)/ (n − ptl + 0.5)]; n: total number of samples in a given bin), and the time course of looking was modeled with four orthogonal polynomial time terms (e.g., Garrison et al, 2020;Mahr et al, 2015), examining for their interaction with condition. We included intercepts and slopes for subjects as random effects (after Garrison et al, 2020).…”
Section: Open Mind: Discoveries In Cognitive Sciencementioning
confidence: 99%